Simulation Analysis on Launch Dynamics of Portable Rocket Launcher Using DEM and FEM. Issue 1 (1st September 2022) - Zhu, Jun; Zhou, Guodong; Fan, Le; Yu, Cungui
Abstract : Spade is an important structure to improve stability of rocket weapons. In order to solve the problem of low precision in numerical simulation of the interaction between a portable rocket launcher and spade and soil, a method combining discrete element and finite element is proposed. A discrete method model of the spade-soil interaction was established to obtain the vertical resistance of soil to the spade. On this basis, a finite element model containing portable rocket launcher, spade and soil was established, and the dynamic response of portable rocket launcher under the launch load was numerically simulated. The results show that the combination of discrete elements and finite elements can accurately simulate the relationship between portable rocket launcher and spade and soil, and the effect of spade on the stability is significant. The combination of discrete element method and finite element method provides new ideas for dealing with the problem of contact between structural members and soil, and it will provide guidance for future model construction and analysis of this kind problem.